The Unique Names of Traditional Foods in Klaten: A Semantic Analysis - Cucut Annaningtyas; Sri Wahyuni Samaratul Z (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This article examines the unique names of traditional foods from the past in Klaten, using a semantic analysis perspective. Traditional foods passed down through generations not only possess distinctive flavors but also carry deep meanings within the local cultural context. This research employs a qualitative approach with data collected through interviews with local community members, culinary practitioners, and cultural figures, as well as documentary studies of written records, archives, and previous literature on traditional foods. The focus is on food names such as Nasi Liwet, Gudeg, and Klepon. Semantic analysis is conducted to understand the relationship between names and the characteristics of the foods, as well as the meanings embedded within them. Findings indicate that many food names in Klaten are inspired by ingredients, cooking methods, or social and cultural contexts, reflecting the identity of the community. This article aims to contribute to the preservation of culinary culture and provide deeper insights into the significance of traditional food names.